Problematika dan Tantangan Penegakan Putusan Litigasi Kenegaraan dalam Sistem Hukum Indonesia - Natanael, Joel; Sari, Marshella Putriana (SAKOLA: Journal of Sains Cooperative Learning and Law, 2025)
The enforcement of state litigation rulings in Indonesia continues to face significant challenges, particularly when the state, as the losing party, refuses to comply with court decisions. This study aims to analyze the core problems in enforcing such rulings and to formulate normative recommendations to strengthen their executory power. Using a qualitative approach and literature review, the research identifies key obstacles such as high levels of corruption, limited resources among law enforcement institutions, and unequal access to justice between the wealthy and the poor. One proposed solution is the reinforcement of Law No. 5 of 1986 on Administrative Court as a normative foundation to ensure state compliance with judicial rulings. The study highlights the importance of institutional support and a strong legal culture to establish a fair, effective, and democratic judicial system.